Acceptability and feasibility of pre-exposure prophylaxis for bacterial STIs: a systematic review. - Julie-Anne Carroll; Amy B Mullens; Sarah Warzywoda; Philip R A Baker; Meika Stafford; Faye McMillan; Jacintha Manton; Daniel Demant (PLoS ONE)
Background A recent resurgence of bacterial sexually transmitted infections (STIs) is placing a major burden on high-risk populations, physicians, and the healthcare system. Treatment in the form of antibiotic pre-exposure prophylaxis (STI PrEP) is a potential solution. However, little is known about the acceptability and feasibility of this approach in high-risk populations. Methods A comprehensive search strategy was developed and executed in October 2024 across six databases adhering to PRISMA guidelines. Results Eight studies met the inclusion criteria. These studies were all conducted in high-income countries, used various methods, and all focussed on sexual minority men. Findings consistently identified moderate to high levels of acceptability among GBMSM (54.3% - 67.5%). Factors such as engagement in perceived 'high risk' sexual encounters, and past diagnosis of STIs strengthened acceptability, while others (e.g., antimicrobial resistance concerns and stigma) act as barriers. Only one study included the perspectives of healthcare workers, indicating a moderate willingness to prescribe, which would increase under governing-body endorsement. Discussion Overall, while there is some promise of STI PrEP acceptability among GBMSM, vast gaps in knowledge remain. Knowledge transfer and feasibility and, hence, the sustainability and capacity needed for the success of STI PrEP is yet to be examined and understood. However, for STI PrEP to be successfully adopted, it is essential not only to assess its acceptability and feasibility but also to focus on knowledge transfer. Knowledge transfer is a dynamic and iterative process, involving the synthesis, dissemination, exchange, and application of knowledge in an ethically sound manner. This process supports the improvement of health outcomes, strengthens healthcare systems, and ensures that healthcare interventions, such as STI PrEP, are effectively understood and implemented by both healthcare providers and at-risk populations. Similarly, the perspectives of populations beyond GBMSM have been omitted, and there is little understanding of the impact of their differing socio-cultural contexts around sex-related behaviour and Western pharmaceutical healthcare interventions on their acceptance and uptake. Conclusion Further research into acceptability, feasibility and knowledge transfer among diverse high-risk groups, healthcare professionals, and policymakers is necessary to create a strong foundation for implementing STI PrEP.